Essays on International Spillovers of monetary policy - Cotarelli, Natalia Quiroga (2022)
This doctoral dissertation is composed of three articles focused on analyzing international spillovers of monetary policy. The first article investigates the spillover effects of monetary policy among OECD countries. First, it appears that, more recently, monetary policy decisions diverge from those indicated by the Taylor Rule. Thus, the article aims to verify if there is a spillover effect in the interest rate decisions of central banks. We apply the methodological framework of spatial econometrics to circumvent the endogeneity problem. Considering the SAR model and a W weight matrix that shows the trade relationship between countries, it is found that countries take into account the international interest rate, besides considering the differential between inflation and its target and the output gap. In the second article, based on classical DSGE models, we analyze the spillover effects of monetary policy by including the foreign interest rate in the domestic monetary agent\'s decision process. The model shows that the relationship between domestic and foreign interest rates depends on the parameters used, particularly the intertemporal elasticity of consumption and the country\'s degree of openness. Considering reasonable values for these parameters, we found a positive relationship between the foreign and domestic rates. Furthermore, in the model estimated for Brazil considering the Taylor Rule with Consumer Price Index (CPI), it was found that a negative shock in the US interest rate generates a drop in the Brazilian rate, stimulating activity and consumption. Therefore, domestic prices rise. However, the CPI declines with the appreciation of the exchange rate, leading to a slow return of the interest rate to the steady state. The third paper seeks to measure the welfare costs generated by the spillover effects of monetary policy. Starting from a non-linear model, we apply the methodology proposed by Schmitt-Grohe and Uribe (2004b) and found that regardless of the importance of the foreign interest rate in domestic decisions, the optimal monetary policy is consistent with an aggressive response of interest rates to inflation and a more mild reaction to the output gap. Comparing different rules, we found some evidence that the central bank incurs social welfare loss when considering the international interest rate. Finally, it is worth noting that the cost depends on the Taylor Rule\'s coefficients and, to a greater extent, on the degree of openness of the economy.